Impalement and anorectal injuries in childhood: a retrospective study of 12 cases - Beiler, Hans Albert; Zachariou, Zacharias; Daum, Roland (Journal of pediatric surgery, 1998)
Background/Purpose: Because of the small numbers of impalement and anorectal injuries in childhood, a standardized therapeutic approach is necessary to avoid major complications. On the basis of a retrospective analysis of 12 children with such injuries treated from 1986 to 1996 in our department, the authors tried to establish guidelines for their treatment. Methods: Additional therapeutic problems and main complications are elucidated after meticulous analysis of three selected cases. Results: In two cases of anorectal impalement and a primary colostomy, no complications occured. However, in three cases involving anorectal injury a primary fecal diversion was not performed, making a secondary colostomy necessary after wound infection. Conclusions: The current standard principles in the treatment of severe anorectal injuries in children are fecal diversion, wound drainage, and broad spectrum antibiotics. A primary reconstruction in cases of impalement can be recommended only after exclusion of anorectal injury.
Elektronische Reproduktion der Druck-Ausgabe 23. Juni 2004
Gesehen am 10.09.2024